Anecdote Research - Peterlini, Hans Karl; Rathgeb, Gabriele (Bloomsbury Publishing (UK), 2026)
This open access book introduces anecdote research to new and experienced researchers by guiding them through its history, theory and underlying principles before delving into step-by-step practical guidance on how to do anecdote research. Anecdote research is an innovative qualitative, narrative and phenomenologically-oriented research methodology that has now gained international recognition, sparking interest from a wide range of institutions, contexts and individuals. Anecdotes are concise, noteworthy stories in which particularly impactful events are condensed by the researcher from transcribed interviews, conversations and impromptu narratives. They can be used in a range of research contexts looking at meaningful recalled experiences, and are especially relevant for longitudinal studies. The eBook editions of this book are available open access under a CC BY 4.0 license on b loomsburycollections.com. Open access was funded by the Austrian Science Fund (FWF) .